2018
DOI: 10.1016/j.chieco.2017.06.004
|View full text |Cite
|
Sign up to set email alerts
|

No longer left-behind: The impact of return migrant parents on children's performance

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 41 publications
0
5
0
1
Order By: Relevance
“…Zhou et al (2014) evaluated the influence of parents' absence on children's Chinese scores and math scores and found that left-behind boys had significantly worse scores in math and Chinese, but no such effect was found for girls. Liu et al (2018) estimated the heterogenous effects of returning migrant parents on the academic achievement of rural children. Their outcomes show that in terms of school performance, girls benefitted more than boys from the return of migrant parents.…”
mentioning
confidence: 99%
“…Zhou et al (2014) evaluated the influence of parents' absence on children's Chinese scores and math scores and found that left-behind boys had significantly worse scores in math and Chinese, but no such effect was found for girls. Liu et al (2018) estimated the heterogenous effects of returning migrant parents on the academic achievement of rural children. Their outcomes show that in terms of school performance, girls benefitted more than boys from the return of migrant parents.…”
mentioning
confidence: 99%
“…In China, Fan (2008, p. 92) found that grandparents are good caregivers for preschool-age children, but older leftbehind children need more direct supervision from their parents. A growing body of research has indicated that having parents who migrate has a significant and negative impact on the development of left-behind children in rural China, especially in terms of school engagement (Wen and Lin, 2012), academic outcomes (Li et al, 2017;Liu et al, 2018), subjective wellbeing (Chai et al, 2019) and mental health (Zhang et al, 2019). Many rural parents therefore choose to reunite with their children in cities in order to provide direct and intensive parental care.…”
Section: Contextual Factors Influencing Rural Migrant Parents' Settle...mentioning
confidence: 99%
“…Social isolation and high physical and psychosocial deprivation increase their risk of mental health outcomes [ 11 , 43 ]. In China, some migrant parents choose to return home when their children start school (around age 6) to support their children emotionally and help them succeed in school [ 16 ]. Previous studies have shown that children who experienced parent–child separation are at a high risk of developing psychological problems during the COVID-19 pandemic [ 34 ] and after lifting the restrictions [ 25 ].…”
Section: Introductionmentioning
confidence: 99%